Reconstructing Women’S Productive Spaces in Contexts of Migration. Violence and Labor Dynamics Through the Analysis of Judicial Sources in the City of Punta Arenas, Xix-Xx Centuries [Reconstruyendo Espacios Productivos de Mujeres en Contextos de Migración. Violencias y Dinámicas Laborales a Través del Análisis de Fuentes Judiciales en la Ciudad de Punta Arenas, S. Xix-Xx1] - Margarit-Segura, D; Boric-Bargetto, L (University of Warsaw, 2021)
This article reflects on the process of the proletarianization of migrant women in the Magallanes region in the late nineteenth and early twentieth centuries, prioritizing a conceptual discussion and theoretical perspective around a gender approach, labor dependencies and discourses within the courts, in order to give visibility to migrant women as a historical subject. Through a qualitative analysis of different judicial sources reviewed against the grain, the relationship between the migratory cycle and the labor dynamics of women in the wage system is placed in dialogue. For both immigrant and migrant women from different regions of Chile, the migratory process in the Magallanes region was constituted primarily as an experience of assimilation and integration into a social and economic organization based on relations of force, obedience, and domination. This situation, especially for female migrant working, established a set of oppressions, restrictions, and violence that placed them in a precarious position in the scale of social estimations. © 2021 University of Warsaw. All rights reserved.
Keywords: judicial source; Magallanes; migratory processes; women; work